Co-alignment of supplier quality management practices and cognitive maps – A neo-configurational perspective. Issue 1 (January 2018) - Kosmol, Tobias; Reimann, Felix; Kaufmann, Lutz
Abstract: Much of the previous research on the 'purchasing practice–performance link' rests on the notion of "net effects, " which assumes that specific practices independently of each other impact outcomes. This study challenges this core tenet by adopting a neo-configurational perspective, exploring how different combinations of factors (called "configurations") affect outcomes. Another limitation of extant studies on the 'purchasing practice–performance link' is the narrow focus on practices; more recent behavioral supply management research finds the behavior of managers to be critically influenced by cognitive maps—the lenses through which managers perceive, simplify, and interpret the world. Focusing on supplier quality as a core aspect of the broader 'purchasing practice–performance link', this study explores how configurations of different supplier quality management (SQM) practices and SQM-related cognitive maps help firms to manage supplier quality. It uses fuzzy-set qualitative comparative analysis (fsQCA) to identify SQM configurations and a cognitive-linguistic approach for the computerized text analysis of purchasing managers' cognitive maps in the context of Western companies sourcing from Chinese suppliers. The configurational fsQCA analysis identifies four different configurations associated with overcoming barriers to SQM in emerging markets. SQM-related cognitive maps prove to be a critical component in these four configurations. Highlights: Advances a neo-configurational perspective for PSM research. Uncovers four configurations for managing supplier quality in emerging markets. Identifies SQM-related cognitive maps as critical components of configurations. Shows the need for a co-alignment of SQM practices and cognitive maps. Employs fuzzy-set qualitative comparative analysis (fsQCA).